Overcoming Emesis Gravidarum With Cardamom Essential Oil Aromather - Tuti Sukini; Arum Lusiana; Hirnanda Ria Damayanti (Midwifery and Nursing Research, 2022)
Background: The cause of emesis gravidarum is due to the increase in the hormones estrogen, progesterone, and human chorionic gonadotropin (HCG).There are 70%-80% of pregnant women experiencing emesis gravidarum, namely nausea and vomiting during the first trimester Emesis gravidarum is caused by the increase in estrogen, progesterone, and human chorionic gonadotropin (HCG).If nausea and vomiting are allowed to continue, it can cause adverse effects on the health of the mother and fetus such as chronic energy deficiency, anemia, bleeding and low birth weight. Efforts to overcome nausea and vomiting during the first trimester of pregnancy can be done using aromatherapy, one of which is cardamom essential oil. The purpose of this study was to determine the aromatherapy of cardamom (cardamom) essential oil can overcome the intensity of nausea and vomiting of pregnant women in the first trimester. Methods: The research is Quasy Experimental Design with One Group Pretest Posttest Design and purposive sampling technique as many as 30 respondents. The research instrument used a questionnaire sheet. Data analysis using Wilcoxon test. Results: There was a significant difference between before and after the intervention of cardamom (cardamom) essential oil aromatherapy in overcoming the intensity of nausea and vomiting in first trimester pregnant women with a p-value of 0.00. Conclusion: The results of this study can be used as a complementary treatment for pregnant women who experience nausea and vomiting to improve their condition by using cardamom essential oil aromatherapy.